2017
DOI: 10.1177/1741143217717278
|View full text |Cite
|
Sign up to set email alerts
|

Generation X leaders from London, New York and Toronto

Abstract: Inspired by scholarly calls to focus more intently on the influence of context on leaders' construction and negotiation of identity, this paper draws on evidence from our Economic and Social Research Council (ESRC) project in London, New York City and Toronto. Throughout the paper, we strive to illuminate how the city-based context influences how race/ethnicity is experienced and described. We use social identity theory, organisational fit and in-group prototypes to frame school leaders' explicit discuss race/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The preference of qualitative methods and, particularly, the case study research methodology is observed in various recent studies on school principals’ identity (e.g. Scribner and Crow, 2012; Notman, 2017; Robertson, 2017; Cho and Jimerson, 2017; Edge et al , 2017; Murakami and Törnsen, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The preference of qualitative methods and, particularly, the case study research methodology is observed in various recent studies on school principals’ identity (e.g. Scribner and Crow, 2012; Notman, 2017; Robertson, 2017; Cho and Jimerson, 2017; Edge et al , 2017; Murakami and Törnsen, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Business leaders must be innovative and flexible but also persistent and focused. How leaders handle these equally necessary but at times opposing competencies is affected by the dynamics of gender, race, sexual orientation, and culture (Edge, Descours, & Oxley, 2017;Hoyt & Murphy, 2016;Rosette, Koval, Ma, & Livingston, 2016).…”
Section: Coaching C-suite Executives and Foundersmentioning
confidence: 99%